Polycystic ovary syndrome and inflammatory factors: Possible role of diet - Ava Hemmat; Faezeh Mashhadi; Mohsen Nematy; Nayere Khadem; Ezzat Hajmolla Rezaei; Fatemeh Roudi (Reviews in Clinical Medicine, 2022)
Polycystic ovary syndrome (PCOS) is the most common endocrinological disorder in women of reproductive age. Several studies have shown that inflammation factors have a crucial role in the function of the ovary as ovarian dysfunction can be caused by an imbalance of pro-inflammatory cytokines. Other studies have shown that PCOS patients have high levels of pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), c-reactive protein (CRP(, interleukin-6 )IL-6(, and interleukin-8 (IL-8). Inflammation can be caused by a variety of factors including diet, and diet-induced inflammation can contribute to insulin resistance and atherogenesis as well as ovulation problems in women with PCOS. It is possible to calculate the components of diet and inflammation caused by diet using many different indices. The Healthy Eating Index (HEI) and Dietary Inflammatory Index (DII) are relatively new indices. As HEI is the overall health index for diet and DII indicates the inflammatory index of the diet, it is possible that a person’s diet can be generally healthy but has a high risk of inflammation, so these two indices should be considered together. Furthermore, dietary management of PCOS patients can reduce hyperinsulinemia, hyperandrogenism, and inflammation, which in turn helps to control and reduce disease complications such as infertility.